Detection of species substitution in raw, cooked, and processed meats utilizing multiplex-PCR assay - Muhammad Cahyadi; Nur Aini Dyah Fauzıah; Imam Tubagus Suwarto; Waraporn Boonsupthip (Universitas Gadjah Mada, 2021)
The rise of beef consumption in Indonesia opens an opportunity for “rogue” suppliers to mix beef with other meat species that are relatively cheaper, such as pork, chicken, etc. The aim of this study was to identify pig and chicken meat in raw, cooked, and processed meat products using multiplex-PCR of mitochondrial DNA Cytochrome b gene, which is maternally inherited and widely used for forensic studies. A total of 90 samples-33 raw meats, 33 cooked meats, and 24 meatballs-were used in this study. Each sample was extracted to obtain the DNA genome and this was then amplified using multiplex-PCR. The PCR products were visualized using 2% agarose gel electrophoresis. The results showed that species contained in raw, cooked, and processed meat samples could be identified as indicated by DNA bands at 398, 274, 227, and 157 bp for pig, cattle, chicken, and goat species respectively. This study concluded that species substitution in raw, cooked, and processed meats could be detected using the Cytochrome b gene as a genetic marker through multiplex-PCR assay.